Random fixed points of non-self maps and random approximations. (1997) - Beg, Ismat
Abstract : In this paper we prove random fixed point theorems in reflexive Banach spaces for nonexpansive random operators satisfying inward or Leray-Schauder condition and establish a random approximation theorem.